PERLINDUNGAN HUKUM PIDANA BAGI KREDITUR DALAM PENYELESAIAN KREDIT MACET DENGAN ADANYA PENGGELAPAN JAMINAN FIDUSIA (Studi Hukum Putusan Nomor 257/Pid.B/2018/PN Smn) - PUTRA, BOUWRIS CHARISMA (Dinamika Hukum, 2020)
PT. Clipan Finance is one of the Sleman branch auto loan financing companies, amid the business benefits that the company receives and the ease with which the consumer can actually lead to new problems, namely the possibility of embezzlement. The embezzlement of car loans from finance companies by the public is very detrimental to the finance company. The public car loans in companies with an installment payment system in the agreement within a certain time. In fact, after the credit agreement ran, many people had bad intentions by not doing their obligation to pay installments. They even divert collateral by selling, pawning, exchanging or renting it out without the knowledge of the company.. The results showed that the legal consequences arising that the debtor can be categorized as committing acts of default and can be prosecuted for embezzlement as Article 372 of the Criminal Code that regulates overall embezzlement of collateral objects that provide sanctions for acts of abuse of rights is relevant to Article 36 of the Guarantee Act Fiduciary which mentions fiduciary givers who transfer, pawn, or lease objects that are objects of fiduciary security or without prior written approval from the fiduciary recipient. Keywords: Settlement of Bad Credit, Fiduciary Guarantee, Embezzlement